Risk correlates of acute respiratory infections in children under five years of age in slums of Bankura, West Bengal - Gupta, Avisek; Sarker, Gautam; Pal, Ranabir (Indian Journal of Child Health, 2014)
Background: Acute respiratory infections (ARI) are the leading cause of mortality and morbidity globally in children under five years of age. Objective: To find out prevalence and risk factors of ARI among under five children. Methods: A population based analytical cross-sectional study was conducted in the urban slums of Bankura, West Bengal on the prevalence of ARI and feeding practices, nutrition and immunization among 152 children under five years of age. Results: Overall prevalence of ARI was 44.73 percent; 43.47 percent male and 45.78 percent female were affected with ARI; half of the infants suffered from ARI (51.21%), it was 45.71 percent in 13- 24 months age groups; with increasing age, prevalence of ARI gradually decreased. ARI was seen in 45.76 percent of exclusively breast fed children and 57.89 percent in children with breast feeding less than six months; in bottle fed children ARI prevalence was 47.82 compared to 44.18 percent in breast-fed. Risk of ARI is almost equal in normal participants and undernourished children. ARI cases were seen among 38.73 percent of completely immunization in comparison to 80.00 percent of partially-immunized children (X2=4.97, p=0.026). Conclusion: The present study had identified a high prevalence of ARI in children less than five years of age. In our study population, ARI was significantly associated with immunization status, but not with feeding practices and nutritional status of the child.